Challenges and Prospects of Community Based Eco-Tourism in Maichew Cluster, a Case of Ofla Woreda - Gebremariam, Kassaye Zewdie (Edelweiss Applied Science and Technology, 2018)
The main objective of this study was to assess the challenges and prospects of community-based ecotourism in the Maichew cluster, a case of Ofla woreda. Community based eco-tourism has become rapidly the most fundamental in-strument to meet sustainable tourism and livelihood option demand across the world at large and Developing Countries in particular. In order to achieve the objective of the study, both primary and secondary data were generated by employing qualitative (using case study, focus group discussion, in depth interview and on spot observation) and quantitative (mainly using household survey and visitor survey questionnaires) methods. Purposive and simple random sampling techniques were used to select 3 CBET sites and 90 sample households respectively. The quantitative data was analyzed using fre-quency, percentage and mean when appropriate while qualitative data was used to triangulate and substantiate the study. The research investigated the challenges for developing CBET in the study area. On the other hand, the study also identified several potentials of CBET in the study area. In addition, the issues for empowering community based eco-tourism in terms of economical, social, political any psychological empowerment was identified. The result of the study reveals that several challenges for empowering community based tourism in the study area, Low level of knowledge, interest and perception of local community towards CBET; the resource ownership questions like land; capacity problems of the MCs and local level government office staff; lack of legal registration of CTEs; conflicting policies and legislations; communities expectation for immediate financial benefits; quality and standard of products and services; lack of cooperation among stakeholders; emerging challenges on marketing and booking; etc. However, several opportunities like strategic location of the sites, change of local attitude toward CBET, hospitality of local community, the potential tourism resources of the area, successful efforts on marketing and promotion, etc. are identified as a positive factor for CBETE. The issues of CE process is in its infant stage despite local communities showed high interest levels to involve in identifying problems, management, decision-making, problem solving, equitable benefit sharing and tourism operation. Thus, economical, social, political and psychological empowerments of community are not well practiced. To conclude, even if community empowerment can play central role to achieve sustainable tourism development and livelihood option, the process is very limited and in its infant stage in terms of economical, social, political and psychological empowerments.